ANALISIS USAHA, NILAI TAMBAH, DAN KESEMPATAN KERJA AGROINDUSTRI TAHU DI BANDAR LAMPUNG - Rosita Rosita; Agus Hudoyo; Achdiansyah Soelaiman (Lampung University, 2019)
The objectives of this study are to analize the business, the added-value and employment of the tofu agroindustry in Bandar Lampung. This study was conducted in Gunung Sulah and Kedamaian villages which are the tofu production centers. The respondents are randomly chosen. The data are processed by using the financial analysis and the value-added analysis. There are two kinds of tofu, i.e the kopong tofu dan the cina tofu. The average net revenues over the cash costs were Rp10.49 million/month of the kopong tofu and Rp12.10 million/month of the cina tofu. The average net revenues over the total costs were Rp4.02 million/month of the kopong tofu and Rp5.17 million/month of the cina tofu. The average standard costs were Rp16,949.97/kg of the kopong tofu and Rp9,206.70/kg of the cina tofu.The average added-value was Rp5,109.31/kg soybeans and its 95 percent confidence interval was Rp2,864.23-7,354.39/kg soybeans. The employment in the two tofu production centers was 143 people.Key words: added value, agroindustry, business analysis, employment, tofu